The Pengaruh Keteladanan Guru Pendidikan Agama Kristen Terhadap Meningkatnya Sikap Belajar Siswa Kelas VIII SMP Negeri 2 Batang Kuis Satu Atap - Purba, Widya; Siregar, Nurliani; Butarbutar, Imelda (NUSRA : Jurnal Penelitian dan Ilmu Pendidikan, 2025)
This study aims to analyze the role model of teachers in improving the learning attitudes of students of SMP Negeri 2 Batang Kuis Satu Atap. This study is a type of quantitative research, the population of this study were Protestant Christian students of class VIII of SMP Negeri 2 Batang Kuis Satu Atap, because the total number of students at SMP Negeri 2 Batang Kuis Satu Atap is 30 people, so the population is people who are role models of PAK Teachers. In this study, the measurement scale used was the Likert scale with the SPSS 25 analysis tool. The results of this study indicate that the sig value of PAK Teacher Exemplar is 0.000 with a t count of 18.278. This means that partially PAK Teacher Exemplar has a positive and significant influence on Student Learning Attitudes, because the significant value is 0.000. Christian religious education is very important to guide students in a better direction, because Christian religious education focuses on the teaching of the Bible which is the highest authority. Therefore, Christian religious education teachers must have a sincere attitude in their teaching, namely teachers become role models in terms of knowledge, attitudes and in many ways for their students. Therefore, a teacher must always reflect a proper and decent life as a good example for his students.